Romantisme Pendidikan Pesantren di Era Milenial dan Revolusi Industri 4.0 - Abas, Abas; Auliya, Hilyatul (CV Kalimasada Group, 2023)
Pesantren, which is the main pillar of the archipelago's original education, is currently often considered a conservative and outdated education, especially in this millennial era. Technological advances in the era of the industrial revolution 4.0, as well as massive globalization and westernization are both challenges and opportunities for kiai and santri in spreading friendly and universal da'wah. The research method used by the author is library research. The author collects various library data to obtain answers to the questions asked by the author. Through the data that the author has collected, the author finds various facts. First, the millennial era can be called the post-modern era. This era is defined by some experts as the era of back to spiritual and moral or back to religion. Meanwhile, the Industrial Revolution 4.0 is a comprehensive transformation of all aspects of production in industry through the merger of digital and internet technology with conventional industries. In this era, information can be spread quickly because all entities are always connected to each other. Second, pesantren experience various dynamics, both social and economic. Pesantren, which is the blue print of Indonesia's original education since hundreds of years ago, does not necessarily make it a static and backward educational institution. In its development, pesantrens do not only teach the yellow book. Nowadays, pesantrens have become an Islamic educational institution that is inclusive and keeps up with the times. Pesantren strives to always open a space for dialog by adopting new values that are more relevant and bring maslahat as well as more perfect in maintaining the existence of pesantren. This is in line with the Al-Muhafadatu 'ala al-Qadimi al-Shalih wa al-Akhdu bi al-Jadid al-Ashlah rule.